Tajdid dan Kebangkitan Islam dalam Perspektif Yusuf Qardhawi: Renewal and Islamic Revival in the Perspective of Yusuf Qardhawi - Azizah, Khansa'; Elhady, Aminullah (Tasfiyah: Jurnal Pemikiran Islam, 2024)
The modern era requires thinkers, including Muslim scholars, to continue to play a role in the people’s development of following the rise of Western civilization since the 18th century. Reform (tajdid) is an expression that describes serious and continuous efforts to deal with this problem. The existence of an understanding that is contrary to these efforts can thwart the revival goal of the people. On the one hand, there is a view of conserving religious texts, on the other hand, there is a view encourages religion to adapt to the orientation of the human life. Yusuf Qardhawi is a contemporary scholar who is very authoritative in addressing the phenomena that occur through a number of his works which assess the importance of the wasat}iyyah principle in initiating reform. This literature study uses a qualitative approach concludes that the realm of reform (tajdid) for Qardhawi is the change of something from one situation to a better and more important condition (including reform of faith, reform of understanding, reform of fiqh and the law therein, as well as reform of preaching). This whole thing cannot be separated from the Al-Qur'an and Sunnah as the foundation for maintaining the principle of balance. For him, anything that is separated from the provisions of Divine revelation and only relies on human abilities will tend to produce contradictions. A reform (tajdid) concept that does not maintain the originality of revelation will create a pseudo-reform. Because according to him, the revival in the phase called “Ushwah Islāmiyyah” requires every Muslim to cultivate love for the religion by believing in the perfection of its teachings without feeling inferior or dazzled by other civilizations.